Analisa Konstruksi Sosial Implementasi Akuntansi Keuangan Untuk Usaha Mikro, Kecil dan Menengah - Ade Palupi; Nada Salsabila (Jurnal Eksplorasi Akuntansi, 2021)
This research takes the lens that the implementation of accounting in micro, small and medium enterprises (MSMEs) into social construction uses a theoretical framework that reviews accounting from the context of its implementation (Hopwood, 2013). The purpose of this research is to prove that accounting practices are the result of mutual relationships between accounting, organizations and institutions, especially in accounting practices in MSMEs. The research approach uses qualitative methods by interviewing fifteen MSME business actors spread across Java and Kalimantan. The results of this study concluded that the interaction of accounting institutions and social factors in the implementation of accounting in MSMEs has not been dynamic and optimal. However, accounting institutions in MSMEs have been formed pragmatically but yet normatively because its implementation has not been conformed to SAK EMKM. Currently MSMEs apply accounting in accordance with their knowledge capacity and abilities that are tailored to their business condition. Nevertheless, the benefits of the application of accounting are experienced and MSME business actors believe that accounting can bring economic and social benefits to the development of their business in future.